1989
DOI: 10.1021/bi00449a030
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation-related conformational change of the membrane-associated coat protein of bacteriophage M13

Abstract: The state of the coat protein of bacteriophage M13, reconstituted into amphiphilic media, has been investigated. The in situ conformation of the coat protein has been determined by using circular dichroism. Minimum numbers for the protein aggregation in the system have been determined after disruption of the lipid-protein system and subsequent uptake of the protein in cholate micelles. The aggregational state and conformation of the protein were affected by (1) the method of coat protein isolation (phenol extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
122
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(134 citation statements)
references
References 44 publications
12
122
0
Order By: Relevance
“…complexes has previously been shown to be essentially the same as the CD spectrum of pVIII in lipid bilayers [23,26--28]. These CD spectra are consistent with about 50-60% helix [26][27][28], which agrees with a Raman estimate of 55% helix using the amide I band [6]. The Raman studies indicated that the SDSpVIII complexes contain a mixture of helix, turns and random, with very little sheet [6], suggesting a transmembrane helix and nonhelical ends for the lnembranebound form.…”
Section: And Roman Spectrasupporting
confidence: 68%
“…complexes has previously been shown to be essentially the same as the CD spectrum of pVIII in lipid bilayers [23,26--28]. These CD spectra are consistent with about 50-60% helix [26][27][28], which agrees with a Raman estimate of 55% helix using the amide I band [6]. The Raman studies indicated that the SDSpVIII complexes contain a mixture of helix, turns and random, with very little sheet [6], suggesting a transmembrane helix and nonhelical ends for the lnembranebound form.…”
Section: And Roman Spectrasupporting
confidence: 68%
“…M 13 coat protein when reconstituted in phospholipid systems is able to adopt different aggregation states depending on its lipidic environment and history of preparation (Spruijt et al, 1989;Spruijt & Hemminga, 1991). Therefore, the aggregation state of the protein was checked in the various reconstituted lipid-protein systems.…”
Section: Resultsmentioning
confidence: 99%
“…The coat protein in a predominant /3-sheet conformation appears to be aggregated in an irreversible way (/3-polymeric protein). The presence of either one of these M l3 coat protein forms depends on the protein purification procedure and reconstitu tion conditions (Spruijt et al, 1989;Spruijt & Hemminga, 1991). M l3 coat protein in the a-oligomeric form is assumed to be the biological active form in membraneassociated processes (Spruijt & Hemminga, 1991;Hemminga et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…15NH,Cl and ["C]glucose were used as the bole carbon and nitrogen sources to obtain uniformly "Nand "C-labelled M13 phages. The isolation and purification of the phages were performed as described earlier (Konings, 1980;Spruyt et al, 1989). Separation of gVIIIp from the phage particles was carried out by phenol extraction (Knippers and Hoffman-Berling, 1966;Konings et al, 1970).…”
Section: Methodsmentioning
confidence: 99%